Presupuesto Participativo, Herramienta de Deliberación y Construcción de Acuerdos entre el Estado Colombiano y la Sociedad Civil (2023)
Participatory budgeting as a democratic activity in which authorities and citizens define how and in what to invest local government resources is based on the citizen's right to participate actively and responsibly in decision-making regarding distribution. Of said resources. This mechanism began in Colombia during the decade of the eighties under the premise of serving as a strengthener of democracy in the country, under Law 1757 of 2015, which contemplates in its articles 90 to 93, the provisions concerning the issue and establishes the framework of its agreements for its application in accordance with the Territorial Development and Territorial Planning Plan (PD and OT) based on the local reality, based on the political constitutional exercise of Colombia, through the implementation of two models, the first of rationalization of political decisions and the second of strategic or conversational action. In addition to this, its construction process defines the establishment of political. objectives, the definition of economic resources, the technical team, the actors and alliances and the participation model as steps for its structuring and materialization.